2023
DOI: 10.3390/app13021118
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dynamics in Metallic MEMS Cantilevers—Pull-In Voltage and Actuation Speed

Abstract: For different metals and varying geometries, this paper presents simulations of electrostatically actuated MEMS cantilevers regarding their influence on pull-in voltage and actuation speed. Three-dimensional electromechanical modeling including many non-linearities has been performed to study some static but mainly dynamic features. The results show that the involved parameters have different influences on the actuation speed and pull-in voltage: lower length, higher thickness as well as lower density and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The measurement presents the highest closing speed of our microshutter arrays measured up to now. In this case, the dimensions of a single microshutter are 2000 µm × 40 µm (Lx and Ly) and the step voltage profile switches from 0 V to 80 V. Our simulations have shown that by reducing the microshutter dimensions (Ly) perpendicular to the hinge, the switching time decreases [51]. However, the height of the actuation voltage also impacts the closing time of the microshutter arrays.…”
Section: Mems Microshutter Arrays For Laser Safety Gogglesmentioning
confidence: 89%
See 2 more Smart Citations
“…The measurement presents the highest closing speed of our microshutter arrays measured up to now. In this case, the dimensions of a single microshutter are 2000 µm × 40 µm (Lx and Ly) and the step voltage profile switches from 0 V to 80 V. Our simulations have shown that by reducing the microshutter dimensions (Ly) perpendicular to the hinge, the switching time decreases [51]. However, the height of the actuation voltage also impacts the closing time of the microshutter arrays.…”
Section: Mems Microshutter Arrays For Laser Safety Gogglesmentioning
confidence: 89%
“…However, the height of the actuation voltage also impacts the closing time of the microshutter arrays. Very low actuation voltages and fast closing cannot be obtained at the same time [51]. A compromise must be found.…”
Section: Mems Microshutter Arrays For Laser Safety Gogglesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Rasid et al conducted in-depth dynamic modeling of micro-lens actuators, emphasizing the need for intricate modeling in designing cantileverbased devices [17]. Yang et al's studies on the modeling and nonlinear dynamics of various cantilever actuators offer perspectives on device behavior under different scenarios, paving the way for design optimization [18]. Lee et al emphasized the critical role of material properties in cantilever-based devices by employing a quasi-static theoretical framework and corroborating their model through quantitative experimental data [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted over two decades to solve this problem, (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) however none of them has achieved a displacement larger than 6 μm at a dc driving voltage typically used in MCU boards. We have focused on this matter and proposed a revolutionary structure that overthrows the conventional structures of electrostatic microactuators, which were considered to be unable to drive large amounts of displacement.…”
Section: Introductionmentioning
confidence: 99%